2020
DOI: 10.5658/wood.2020.48.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Stability, Color Change, and Durability of Boron-MMA Treated Red Jabon (Antochephalus macrophyllus) Wood

Abstract: Boron compound had many advantages as wood preservative, but it was prone to leaching. Improving boron preservation was required to extend the service life of fast growing and low durability red jabon (Antochephalus macrophyllus) hardwood. This study aimed to evaluate the dimensional stability, color change and durability of modified red jabon wood by double impregnation with boron and methyl methacrylate (MMA) and heat treatment. Impregnation I used boric acid or borax, and impregnation II used MMA, while hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Concerning negative reactions to wood, such as "logging" and "expensive," it is vital to shift public opinion via publicity that wood functions as a carbon storage and is a sustainable recycling resource (Lippke et al, 2011). Furthermore, for negative perceptions of wood utilization such as "old material," "difficulty in management," and "chemical treatment," publicity is required to improve negative perceptions by utilizing research results such as strengthening the effect of preservative treatment of wood products (Cahyono et al, 2020;Lee et al, 2020;Priadi et al, 2020) and toxicity analysis of chemicals such as preservatives and flame retardants used in wood.…”
Section: Table 2 Continued Classification Detailsmentioning
confidence: 99%
“…Concerning negative reactions to wood, such as "logging" and "expensive," it is vital to shift public opinion via publicity that wood functions as a carbon storage and is a sustainable recycling resource (Lippke et al, 2011). Furthermore, for negative perceptions of wood utilization such as "old material," "difficulty in management," and "chemical treatment," publicity is required to improve negative perceptions by utilizing research results such as strengthening the effect of preservative treatment of wood products (Cahyono et al, 2020;Lee et al, 2020;Priadi et al, 2020) and toxicity analysis of chemicals such as preservatives and flame retardants used in wood.…”
Section: Table 2 Continued Classification Detailsmentioning
confidence: 99%
“…The previous studies showed that the durability of Samama on rot fungi increased after impregnated with Boron and MMA (Priadi et al 2020). Boron impregnation has been shown to increase the flexural properties of samama wood, with improved results after addition of polymer to reduce leaching.…”
Section: Introductionmentioning
confidence: 97%
“…Materials used to maintain boron fixation include polymers (Priadi et al 2020), tannin (Verly Lopes et al 2020), silicon emulsion (Kartal et al 2007), tall oil derivative (Temiz et al 2008), rosin (Nguyen et al 2020) and egg albumin (Thévenon et al 1998). Vegetable oil has also been used to increase boron fixation in wood (Tomak et al 2011), an approach chosen because vegetable oil is cheap and non- poisonous and forms protective layers on the wood surface (Hyvönen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A potential candidate that solves this issue are waterborne wood preservatives, particularly boron compounds (Augustina et al, 2020;Priadi et al, 2020). Boron compounds are not toxic to humans, and environmentally friendly which are essential for wooden products (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%